2012
DOI: 10.1186/1756-0500-5-392
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone signaling pathway analysis method for comparing hormone responses in plant-pest interactions

Abstract: BackgroundPhytohormones mediate plant defense responses to pests and pathogens. In particular, the hormones jasmonic acid, ethylene, salicylic acid, and abscisic acid have been shown to dictate and fine-tune defense responses, and identification of the phytohormone components of a particular defense response is commonly used to characterize it. Identification of phytohormone regulation is particularly important in transcriptome analyses. Currently there is no computational tool to determine the relative activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…SA signaling pathway was found to mediate an effective defense response with SA-related transcripts induced as early as 6-12 h after aphid infestation in resistant plants compared to susceptible plants (Li et al 2008). Phytohormone analysis (Studham and MacIntosh 2012) to determine the extent of contribution of SA, JA, ET and ABA in plant response to aphids reinforces this finding. Further, a role for ABA as a decoy defense initiated by aphids to suppress activation of SA-mediated defenses was also suggested largely due to the massive induction of ABA-related transcripts in susceptible plants but not in the resistant plants.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…SA signaling pathway was found to mediate an effective defense response with SA-related transcripts induced as early as 6-12 h after aphid infestation in resistant plants compared to susceptible plants (Li et al 2008). Phytohormone analysis (Studham and MacIntosh 2012) to determine the extent of contribution of SA, JA, ET and ABA in plant response to aphids reinforces this finding. Further, a role for ABA as a decoy defense initiated by aphids to suppress activation of SA-mediated defenses was also suggested largely due to the massive induction of ABA-related transcripts in susceptible plants but not in the resistant plants.…”
Section: Introductionsupporting
confidence: 65%
“…MeJA not SA pretreatment reduces aphid populations Gene expression analysis from previous studies (Li et al 2008;Studham and MacIntosh 2012) and the current study suggests that SA-related genes are induced in response to soybean aphids (Fig. 2a).…”
Section: Meja Treatment Reduces Thrips Populationsmentioning
confidence: 58%
“…The reduction in PUFA under SBA infestation could partly be responsible for suppression of JA defense responses by limiting precursors of the JA pathway. This hypothesis of JA suppression by SBA is supported by a similar result by [50] who showed that long term exposure of soybean to SBA results in suppression of the JA response. Since there was an increase in expression of JA biosynthesis genes without a corresponding increase in the JA response, we also hypothesize that control of fatty acid metabolism in this system could be posttranscriptional.…”
Section: Ja Response In Arabidopsis Was Significantly Suppressed Uponsupporting
confidence: 60%
“…We conducted an analysis of previous microarray data generated in the lab [50] to examine the effect of aphid infestation on expression of JA biosynthesis and response genes in soybean. While the biosynthesis genes were examined together, JAR1 was used to investigate the response to JA.…”
Section: Expression Of Ja Biosynthesis Genes and Jar1 A Ja Response mentioning
confidence: 99%
“…In this framework, it is known that jasmonic acid (JA) and its metabolites, collectively known as jasmonates (JAs), are plant growth inhibitors, mainly involved in counteract biotic stress, i.e. against herbivore and pathogen attack (Antico et al 2012;Studham & MacIntosh 2012). Earlier observations reported the inhibition of primary root growth in Arabidopsis seedlings grown on media supplemented with 0.1 µM methyl jasmonate (MeJA) (Staswick et al 1992).…”
Section: General Mechanism Of Interaction Between Auxin and Jasmonatesmentioning
confidence: 99%